DIFFICULTIES AND TREATMENT OUTCOMES OF ORTHODONTIC THERAPY OF A PATIENT WITH WILLIAMS SYNDROME - Elif Dilara Şeker; Türker Yücesoy; Ahmet Yağcı (Selcuk Dental Journal)
Williams Syndrome (WS) is a rare congenital and progressive multisystem disorder which is described with specific systemic disorders, skeletal and dental abnormalities and tongue thrusting. A 13-year-old patient applied to our clinic with complaining dental caries, malocclusion and tongue thrusting. The patient was treated with a full fixed standard edgewise appliance named as Mini Master Series from American Orthodontics (Central Islip, N.Y., USA), 0.018 inch bracket slots) for 2 years and 8 months.